1997
DOI: 10.1007/bf01880673
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 2, heparin and suramin reduce epithelial ulcer development in experimental HSV-1 keratitis

Abstract: These experiments demonstrate that FGF-2 is effective in promoting herpetic epithelial ulcer healing, either due to its proliferative effects on epithelial cells or indirectly by occupying the sites on cell surface heparan sulfate necessary for the attachment of the virion. The latter mechanism of action is presumably the reason for the similar effect of heparin and suramin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It has been previously reported that a receptor for basic FGF serves as a receptor for HSV-1 (19), and Fgfr3 and Fgfr4, a candidate gene on chromosome 13, could act as such receptors. Not surprisingly, there have also been many studies describing the importance of FGF in keratitis (14,36). Another candidate gene, Fgf14 or Fhf-4, on chromosome 14, shown to be important in the nervous system (39,47), could play a role in herpesvirus infectivity.…”
Section: Discussion Hsv Infectionsmentioning
confidence: 99%
“…It has been previously reported that a receptor for basic FGF serves as a receptor for HSV-1 (19), and Fgfr3 and Fgfr4, a candidate gene on chromosome 13, could act as such receptors. Not surprisingly, there have also been many studies describing the importance of FGF in keratitis (14,36). Another candidate gene, Fgf14 or Fhf-4, on chromosome 14, shown to be important in the nervous system (39,47), could play a role in herpesvirus infectivity.…”
Section: Discussion Hsv Infectionsmentioning
confidence: 99%
“…Several studies with a rabbit SK model also showed that FGF-2 protein treatment induced ulcer healing with reduction of inflammation in the cornea. 18,19 Although we did not formally show how it actually worked in the current study, previous studies have demonstrated that FGF-2 specifically binds to denuded corneal epithelial basement membrane 20 and efficiently induces wound healing of the corneal epithelium. 14,21 Because FGF-2 has the ability to induce cell proliferation and migration, 22,23 topical application of FGF-2 into the cornea may promote the proliferation of corneal epithelial cells resulting in accelerating wound healing.…”
Section: Discussionmentioning
confidence: 59%
“…10,16,17 In addition, in vivo studies using a rabbit model have shown that recombinant FGF-2, heparin, or suramin treatment after viral infection reduced epithelial ulcer development in SK but did not have a significant antiviral effect. 18,19 In our experimental model, we administered high concentration of DNA encoding FGF-2 or protein before virus infection, but its antiviral effects were temporary. It is believed that FGF-2 protein is not continuously or stably expressed for several days, because this protein may be degraded within a short period or easily washed by tears.…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] It may accelerate wound repair and protect the matrix. [18,19] The effects of bFGF on various biochemical changes in the inflammatory response at the molecular level can inhibit the proliferation of lymphocytes by IL-1 and IL-2, the generation of cytokines, the expression of antigen-like enhancers that are enhanced by interferon, and the expression of activator B of the complement bypass pathway induced by cytokines. [20] The alleviation of inflammation can protect burn wounds and reduce wound sepsis and SIRS.…”
Section: Discussionmentioning
confidence: 99%